2011
DOI: 10.2478/s11536-011-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage scan of major depressive disorder in two Dagestan genetic isolates

Abstract: AbstractWe conducted a 10-cM genome-wide linkage scan in two extended pedigrees, ascertained from two diverse Dagestan genetic isolates with high aggregation of major depressive disorder (MDD) and suicides. Using genome wide multipoint parametric linkage analyses with short tandem repeat markers, we found two previously undetected genomic regions with significant linkage in isolate #6007 with LODs=3.1–3.4 at 2p13.2–p11.2 (and some signal in same region for #6008) and in 14q31.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Three genomic regions we found linked to ID: 11q23, 12q24.23-q24.32 and 22q12.3-q13.1, have previously been reported to be associated with SCZ and MDD (Bulayeva et al, 2007; 2011; 2012). The genomic regions linked to this spectrum of clinical phenotypes were also confirmed by MRI findings in SCZ (Simic et al 1997).…”
Section: Discussionmentioning
confidence: 64%
“…Three genomic regions we found linked to ID: 11q23, 12q24.23-q24.32 and 22q12.3-q13.1, have previously been reported to be associated with SCZ and MDD (Bulayeva et al, 2007; 2011; 2012). The genomic regions linked to this spectrum of clinical phenotypes were also confirmed by MRI findings in SCZ (Simic et al 1997).…”
Section: Discussionmentioning
confidence: 64%
“…30,[32][33][34][68][69][70][71][72][73][74] Several genetic studies of quantitative, disease-related phenotypes have already been successfully carried out in Daghestanian small isolated communities. 30,[32][33][34][69][70][71][72][73][74] These studies observed notable within-and between-isolate diversity in clinical and genetic heterogeneity likely because of differences in founders, subsequent endogamy and inbreeding within the isolates. The results from these studies suggest that mapping genes of complex diseases, including major depressive disorder, schizophrenia, hearing loss across genetically homogeneous isolates, can facilitate detecting linkage signals and expedite the search for susceptibility genes when combined with the methods that identify structural genomic and nucleotide variation in linkage regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, as described above, PRL /6p22.3, PRLR /5p13.2, PRLHR/ 10q26.13, OXT / 20p13, OXTR /3p25, and NPY /7p15.1 genes/loci have all been variably linked and/or associated with prediabetes traits, SCZ, bipolar disorder, MDD, postpartum depression, T2D, C‐reactive protein, T2D‐atherogenic particles, MetS, and CAD (An et al, ; Bespalova et al, ; Bosse et al, ; Bowden et al, ; Breen et al, ; K. Bulayeva et al, ; Divers et al, ; Fallin et al, ; Fanous et al, ; Ghosh et al, ; Gornick et al, ; Jonas et al, ; Kong et al, ; Lakka et al, ; Lu et al, ; Marcheco‐Teruel et al, ; Maziade et al, ; Montag et al, ; Myers et al, ; Nilsson et al, ; Rybakowski et al, ; Smith et al, ; Teltsh et al, ; Teltsh et al, ; Voight et al, ; Y. Wang et al, ; Wiltshire et al, ; Zeggini et al, ; Zintzaras & Ioannidis, ). Furthermore, the PRL , PRLR , PRLHR , OXT , OXTR , and NPY genes play a key role in the PRL‐pathway and may, if impaired, confer risk for T2D, Mets, associated traits, and the SCZ‐T2D and/or ‐MetS comorbidity.…”
Section: Prl‐pathway Genes Mental Diseases and Metabolic Genetic Ovmentioning
confidence: 96%
“…OXT lies on 20p13, a locus linked and/or associated with small atherogenic LDL‐particles, large VLDL‐particles in diabetic subjects (Divers et al, ), T2D (Ghosh et al, ), MDD (K. Bulayeva et al, ), and SCZ (Fanous et al, ; Teltsh et al, ; Teltsh et al, ). OXT is not associated with childhood depression (Strauss et al, ) and is associated with postpartum depression (Jonas et al, ) and SCZ (Montag et al, ; Teltsh et al, ).…”
Section: Prl‐pathway Genes Mental Diseases and Metabolic Genetic Ovmentioning
confidence: 99%